Pengaruh Kepercayaan Merek dana Kualitas Pelayanan Terhadap Loyalitas Pelanggan Shopee dengan Kepuasan Pelanggan Sebagai Pemediasi (Survei pada Mahasiswa Fakultas Ekonomi Unisri Surakarta) - Rochman Nurcholis; Retno Susanti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Shopee is one of the most popular online shopping platforms in Indonesia. The phenomenon that occurs is the gap between the popularity achieved by Shopee today and the service received by consumers. Negative consumer reviews indicate dissatisfaction with complaints experienced by consumers towards the Shopee marketplace. Consumer distrust of the Shopee brand and the poor quality of electronic services trigger consumer dissatisfaction with the Shopee marketplace which will have an impact on customer loyalty. The purpose of this study is to analyze the influence of brand trust and service quality on Shopee customer loyalty through customer satisfaction as a mediating variable. The population of this study were UNISRI Surakarta students who were Shopee customers, where the number was not known for certain. This study used a sample of 100 students calculated using the Leedy formula. The sampling technique used purposive sampling, with the criteria of students who made purchases at Shopee more than 1 time in the last 3 months. The data collection technique used a questionnaire assessed on a 5-point Likert scale. The data analysis technique used path analysis. The results of the analysis show that brand trust has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction, brand trust has a significant effect on customer loyalty, service quality has a significant effect on customer loyalty, customer satisfaction has a significant effect on customer loyalty, customer satisfaction can mediate the effect of brand trust on customer loyalty, customer satisfaction can mediate the effect of service quality on customer loyalty